Studies on the Chemical Control of Psychrophilic Bacterial Spoilage of Fish. iii- The Effect of Chemical Preservatives on the Growth of Psychrophilic Bacteria Isolated from Marine Fish - Anand, C. P.; Setty, T. M. Rudra (Fishery Technology, 1981)
Among the six chemical preservatives tried, propyl and methyl paraben were found to be very effective in inhibiting the growth of all the cultures. While propyl paraben could check the growth of all the cultures at 0.1% level, methylparaben could do the same only at 0.2% level. The other preservatives namely, orthochlorobenzoic acid (upto 0.2%), sodium hypochlorite (upto 25 p.p.m.) ethoidin (upto 0.025%) and polyethylene glycol (upto 4 p.p.m.) had no inhibitory effect on any of the cultures tried.